New insights into the wheat chromosome 4D structure and virtual gene order, revealed by survey pyrosequencing. (April 2015) - Helguera, Marcelo; Rivarola, Máximo; Clavijo, Bernardo; Martis, Mihaela M.; Vanzetti, Leonardo S.; González, Sergio; Garbus, Ingrid; Leroy, Phillippe; Šimková, Hana; Valárik, Miroslav; Caccamo, Mario; Doležel, Jaroslav; et al.
Highlights: Survey sequence of T. aestivum chromosome 4D was obtained by pyrosequencing. Near 5700 genes were predicted on 4D chromosome, ∼2200 on 4DS and ∼3500 on 4DL. A 4D virtual gene order based on synteny with orthologous gene loci is proposed. Among group 4, higher collinearity exists between 4D and 4B as compared to 4A. Complementary data to that provided by IWGSC is presented, available at NCBI. Abstract: Survey sequencing of the bread wheat ( Triticum aestivum L.) genome (AABBDD) has been approached through different strategies delivering important information. However, the current wheat sequence knowledge is not complete. The aim of our study is to provide different and complementary set of data for chromosome 4D. A survey sequence was obtained by pyrosequencing of flow-sorted 4DS (7.2×) and 4DL (4.1×) arms. Single ends (SE) and long mate pairs (LMP) reads were assembled into contigs (223 Mb) and scaffolds (65 Mb) that were aligned to Aegilops tauschii draft genome (DD), anchoring 34 Mb to chromosome 4. Scaffolds annotation rendered 822 gene models. A virtual gene order comprising 1973 wheat orthologous gene loci and 381 wheat gene models was built. This order was largely consistent with the scaffold order determined based on a published high density map from the Ae. tauschii chromosome 4, using bin-mapped 4D ESTs as a common reference. The virtual order showed a higher collinearity with homeologous 4B compared to 4A. Additionally, a virtual map was constructed and ∼5700 genes (∼2200 on 4DS and ∼3500 on 4DL) predicted. The sequence and virtual order obtained here using the 454 platform were compared with the Illumina one used by the IWGSC, giving complementary information.